Cyclostratigraphy and Spectral Analysis of Geophysical Logs - S. Djin Nio (Berita Sedimentologi, 2000)
Stratal patterns and stratification of sedimentary rocks are one of the most remarkable features of sedimentary rocks. Stratification patterns are formed by various periodic, which are episodic depositional processes and sometimes modified and overprinted by biological and diagenetic processes. In outcrop, stratal patterns and stratifications commonly display a certain degree of rhythmicity, representing an alternation or repetition of lithofacies units. These rhythmic and cyclic patterns occur worldwide and are observed in all depositional facies throughout geological time. Cyclostratigraphy is the study of these rhytmic and cyclic patterns in sediment successions.The concept of cyclostratigraphy has developed from a descriptive classification scheme into process-related interpretations. Furthermore, with the development of sequence stratigraphy and the improved seismic acquisition tools for the subsurface, the understanding of climate-related processes and basin dynamics is becoming more clear and is presently considered as the driving mechanism in cyclostratigraphy.This short paper discusses new cyclostratigraphic concepts derived from deterministic modelling of wireline log data.